Effect of inlet temperature and flow rate towards produce 2% carboxymetyl cellulose spray dried powder: article - Md Jais, Nur Sakinah; Abd. Rahman, Norazah (2017)
Carboxymethyl cellulose (CMC) can be synthesized from waste such as empty fruit bunch or sago pulp and is commonly used in detergent and pharmaceutical product. Currently, CMC is delivered in liquid and fibre condition which incurred high cost and difficult to handle. Thus, CMC needs to be converted to powder form for ease handling. A study was done to determine the suitable inlet temperature and flow rate of producing 2% CMC powder by using spray dryer. Results showed the high inlet temperature and low flow rate of pump recovered more powder than low inlet temperature and high flow rate. Then, the research were scale up at pilot plant by using parameters that have been obtained in bench scale. Powder obtained from scale up process were analyzed and it was found that the powder produced at high temperature and low flow rate have low moisture content, low viscosity and less yellowness index (YI) compared with TL100 given by the industry. As a conclusion, high temperature and low flow rate of speed pump are suitable to recover 2% CMC solution synthesized from empty fruit bunch.